Unmet communication needs and moral work in the disposition decision concerning surplus frozen embryos: The perspectives of IVF users. (April 2021) - Raz, Aviad; Vardi, Jasmine; Reisner Vain, Shelly; Meiri, Amir; Barkan, Gali; Azem, Foad; Amir, Hadar
Abstract: The disposition decision is a frequently unresolved issue for many IVF users with surplus frozen embryos (SFEs), and this study draws attention to their experiences and moral work, locating it in the Jewish-Israeli context that legally enables the donation of SFEs to research but prohibits donation to other infertile people. To explore the (mis)understandings and (mis)communication underlying IVF users' decisions concerning the fate of their SFEs, the records of 674 IVF users with SFEs stored for more than 5 years during 1996–2011 were analyzed, and 89 IVF users with different disposition decisions were recruited for semi-structured interviews. With an average of 5.1 SFEs, after an average of 8 years of storage, no response to a written request for a disposition decision came from 60% (n = 404) of IVF users with SFEs. Payment for storage and defrosting were the two most frequent choices (13%, n = 89 and 89, respectively) followed by donation to research and transfer (7%, n = 47 and 45, respectively). Three themes emerged from the interviews: misunderstanding the consequences of not returning the disposition form, communication gaps regarding donation to research, and the unmet wish to donate embryos to infertile people. We conclude by discussing the experiences and views of IVF users as reflecting the implications of the liminality and boundary-work surrounding the frozen embryo as a moral work object, and their consequences for policy recommendations. Highlights: IVF users with SFEs experience unmet communication needs and misconceptions. Many decide not to decide due to unmet communication needs and unfinished moral work. Many decline to donate to research due to lack of communication about the research. Deciding to donate to research was seen by many as the "least bad option". Many support donation to infertile people and would like to see it publicly discussed.